1992
DOI: 10.1093/cercor/2.3.217
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of Pulvinar Neurons That Project to Two Subregions of the Inferior Parietal Lobule in the Macaque

Abstract: The distribution of pulvinar neurons that project to the lateral intraparietal area (LIP) and area 7a, two subregions of the inferior parietal lobule in monkeys, was determined using small injections of retrogradely transported fluorescent dyes. Both LIP and 7a received the majority of their thalamic input from contiguous but distinct zones within the medial pulvinar nucleus. Thalamocortical cell bodies that projected to LIP were arranged in a dense, horizontally oriented cluster that was sandwiched between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
37
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 0 publications
12
37
0
Order By: Relevance
“…Similarly, a dorsal portion of the lateral pulvinar projects to LIP Hardy and Lynch, 1992;Baizer et al, 1993). Our results suggest that neurons in the lateral pulvinar mediate a projection from the superficial layers of the superior colliculus to LIP.…”
Section: Superior Colliculus To Lipsupporting
confidence: 53%
See 2 more Smart Citations
“…Similarly, a dorsal portion of the lateral pulvinar projects to LIP Hardy and Lynch, 1992;Baizer et al, 1993). Our results suggest that neurons in the lateral pulvinar mediate a projection from the superficial layers of the superior colliculus to LIP.…”
Section: Superior Colliculus To Lipsupporting
confidence: 53%
“…Injections of HSV1 into IPL led to dense labeling in thalamic nuclei known to be the origin of input to each cortical region (Kasdon and Jacobson, 1978;Asanuma et al, 1985;Schmahmann and Pandya, 1990;Hardy and Lynch, 1992;Baizer et al, 1993). Labeled neurons were found in other thalamic nuclei as well.…”
Section: Thalamic Labelingmentioning
confidence: 95%
See 1 more Smart Citation
“…Approximately 0.6 l of each fluorescent dye was placed at each injection site. All tracers were pressure-injected (Hardy and Lynch, 1992), using a 1 or 5 l Hamilton syringe. Each injection was made over a 5 min period.…”
Section: Methodsmentioning
confidence: 99%
“…Comparison across studies suggests that the lateral PM is more strongly related to visual processing, by virtue of its connections with posterior parietal and inferior temporal cortex (DeVito and Simmons, 1976;Mauguiere, 1985, 1987;Schmamann and Pandya, 1990;Baleydier and Morel, 1992;Hardy and Lynch, 1992;Cusick et al, 1993;Morecraft et al, 1993;Webster et al, 1993;Romanski et al, 1997), whereas the medial PM is more strongly related to auditory processing, based on preferential connections with auditory areas of the superior temporal region established in the present study and several others (Simpson, 1952;Locke, 1960;DeVito and Simmons, 1976;Trojanowski and Jacobson, 1976;Burton and Jones, 1976;Mauguiere and Baleydier, 1978;Streitfeld, 1980;Markowitsch et al, 1985;Moran et al, 1987;Pandya et al, 1994;Romanski et al, 1997). Most of the studies cited above, among others (Jones and Powell, 1970b;Trojanowski and Jacobson, 1976;Divac et al, 1977;Asanuma et al, 1985;Pandya, 1985, 1989;, have shown that the central PM has connections with auditory, somatic, visual, and multimodal cortical areas, suggesting that the central PM may subserve multimodal integrative functions more than the lateral or medial portions of the nucleus, which appear to be somewhat more modality specific.…”
Section: Medial Pulvinarmentioning
confidence: 99%